Exploring immersion through a fMRI-compatible multi-finger handheld haptic display - Joonsub Byun; Joonseon Hwang; Yong-An Chung; Hyeonseok Jeong; Jooyeon Kim; Keehoon Kim (PLoS ONE, 2026)
This research presents the development and evaluation of a functional magnetic resonance imaging (fMRI)-compatible, handheld, multi-finger haptic display, designed to augment and quantitatively measure immersion within virtual reality (VR) environments via tactile feedback mechanisms. Incorporating advanced pneumatic actuators, the device is capable of delivering differentiated pressure feedback to individual fingers, thereby facilitating a more realistic interaction within VR scenarios. Comprehensive fMRI-compatibility assessments have been successfully conducted, verifying the device’s operational integrity within a 3T functional magnetic resonance imaging (fMRI) setting. This ensures its applicability for integrated neuroscientific explorations. Alongside, a VR platform was implemented to integrate audiovisual stimuli with haptic feedback, aiming to create a fully immersive experience for participants during fMRI studies. Experiments involving human subjects have demonstrated marked cortical activations in brain regions associated with immersive experiences, attributed to interactions with the VR content via the proposed haptic display. These findings highlight the potential of the developed haptic system in both enhancing the immersive quality of VR environments and serving as a novel instrument for the quantitative analysis of immersion through neuroimaging. The study advances the field by offering a new avenue for the exploration of neural mechanisms underlying immersive VR experiences, facilitated by fMRI-compatible haptic feedback.